2006
DOI: 10.1111/j.1468-2982.2006.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Subarachnoid Haemorrhage in a Patient With Spinal Tumour

Abstract: Primary headaches are closely related to sleep. Modifications in the patterns of arousal during sleep have been reported in migraine, especially in the nights preceding a headache attack. We aimed at evaluating the pattern of arousal from sleep in a group of patients affected by sleep-related migraine. We enrolled 10 consecutive patients, three males and seven females, aged between 20 and 62 years, who presented frequent attacks of migraine without aura (more than five per month), closely related to sleep (mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(70 reference statements)
4
6
1
Order By: Relevance
“…This is comparable with previous studies, which also found a reduction of CAP duration in patients with prevalently nocturnal MOA, in the presence of a normal sleep macrostructure [10], or a reduction of K/Dburst index with features of disturbed sleep [25]. Additionally, the phase A2 and A3 indices were decreased in this study, which were not in agreement with the findings of other studies where the reduction in CAP phase was predominantly seen during phase A1 subtype [10]. We also found a significant reduction in the number of CAP cycles and CAP sequences in patients with migraine as compared to controls.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is comparable with previous studies, which also found a reduction of CAP duration in patients with prevalently nocturnal MOA, in the presence of a normal sleep macrostructure [10], or a reduction of K/Dburst index with features of disturbed sleep [25]. Additionally, the phase A2 and A3 indices were decreased in this study, which were not in agreement with the findings of other studies where the reduction in CAP phase was predominantly seen during phase A1 subtype [10]. We also found a significant reduction in the number of CAP cycles and CAP sequences in patients with migraine as compared to controls.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it may be hypothesized that the reduced arousability during REM sleep may result in the failure of brain mechanisms in halting migraine attacks, which may in turn be responsible for the predilection of migraine attacks to occur during this sleep stage. These findings support the conclusions of previous studies, which also found reduction in frequency of arousals during these deeper stages (N3 and REM) of sleep [4,10,19]. Likewise, a reduction in the total CAP rate, as well as a reduction in the amount of cycling from CAP phase "A" to phase "B" and vice versa, alongside decreased A2/A3 indices in our patients with MOA, may show an impaired ability of the brain to terminate an attack of migraine even during NREM sleep.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations